2018
DOI: 10.1088/1361-6579/aaab07
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and early detection of delirium in the intensive care unit by using heart rate variability and machine learning

Abstract: Our results show that autonomic alterations could be a significant feature of patients with delirium in the ICU, suggesting the potential for the automatic prediction and early detection of delirium based on HRV with machine learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 36 publications
1
49
0
1
Order By: Relevance
“…HRV is a simple and non-invasive examination, which can evaluate the activity of autonomic nerve, the energy-saving ability of the body, and the influence of interventions on the function of autonomic nerve in patients [ 48 , 49 ]. Previous studies have shown nearly 70% of PBC patients with autonomic nervous dysfunction [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…HRV is a simple and non-invasive examination, which can evaluate the activity of autonomic nerve, the energy-saving ability of the body, and the influence of interventions on the function of autonomic nerve in patients [ 48 , 49 ]. Previous studies have shown nearly 70% of PBC patients with autonomic nervous dysfunction [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time heart rate variability assisted by ML techniques have been investigated in preliminary studies as a method of delirium identification [17]. Excess sympathetic activity associated with delirium can be detected in real-time by continuous monitoring of vital signs.…”
Section: Delirium Identificationmentioning
confidence: 99%
“…More recent research demonstrates that delirium is often reversible with early detection and treatment. [ 14 15 ] Therefore, it is important to identify related risk factors before surgery and make a dedicated perioperative care path. The Cornell assessment of pediatric delirium (CAPD) is a validated screening tool designed for children of all ages and developmental abilities.…”
Section: Introductionmentioning
confidence: 99%